2015
DOI: 10.1002/jhbp.296
|View full text |Cite
|
Sign up to set email alerts
|

Single‐stage endoscopic treatment for mild to moderate acute cholangitis associated with choledocholithiasis: a multicenter, non‐randomized, open‐label and exploratory clinical trial

Abstract: Background Two-stage treatment involving stone removal after drainage is recommended for mild to moderate acute cholangitis associated with choledocholithiasis. However, single-stage treatment has some advantages. We aimed to assess the efficacy and safety of single-stage endoscopic treatment for mild to moderate acute cholangitis associated with choledocholithiasis. Methods A multicenter, non-randomized, open-label, exploratory clinical trial was performed in 12 institutions. A total of 50 patients with a naï… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 15 publications
0
26
0
Order By: Relevance
“…The TG13 flowchart proposed that for patients with moderate cholangitis, treatment for the underlying etiology should be provided electively after early biliary drainage, and that for patients with mild cholangitis due to choledocholithiasis, treatment for the underlying etiology such as endoscopic sphincterotomy (EST) and choledocholithotomy may be performed at the same time as biliary drainage . Three observational studies (one of which did not use severity assessment criteria) (CS) and one RCT showed that single‐stage lithotomy was safe and feasible in cases of mild or moderate acute cholangitis caused by choledocholithiasis. In the RCT, however, the rate of complications after endoscopic retrograde cholangiopancreatography (ERCP) was significantly higher than that after two‐stage lithotomy (6/35 = 17.1% vs. 0/33 = 0%, P = 0.025) (RCT) ; therefore, caution is required.…”
Section: Flowchart For the Initial Response To Acute Biliary Infectionmentioning
confidence: 99%
“…The TG13 flowchart proposed that for patients with moderate cholangitis, treatment for the underlying etiology should be provided electively after early biliary drainage, and that for patients with mild cholangitis due to choledocholithiasis, treatment for the underlying etiology such as endoscopic sphincterotomy (EST) and choledocholithotomy may be performed at the same time as biliary drainage . Three observational studies (one of which did not use severity assessment criteria) (CS) and one RCT showed that single‐stage lithotomy was safe and feasible in cases of mild or moderate acute cholangitis caused by choledocholithiasis. In the RCT, however, the rate of complications after endoscopic retrograde cholangiopancreatography (ERCP) was significantly higher than that after two‐stage lithotomy (6/35 = 17.1% vs. 0/33 = 0%, P = 0.025) (RCT) ; therefore, caution is required.…”
Section: Flowchart For the Initial Response To Acute Biliary Infectionmentioning
confidence: 99%
“…). Most recently, Eto et al . evaluated the efficacy and safety of single‐step endoscopic treatment for mild to moderate acute cholangitis associated with CBDS.…”
Section: Discussionmentioning
confidence: 99%
“…2). Most recently, Eto et al 8 evaluated the efficacy and safety of single-step endoscopic treatment for mild to moderate acute cholangitis associated with CBDS. As a result, acute cholangitis resolved within 4 days after the endoscopic treatment in 90% of the patients.…”
Section: Diatal Hilarmentioning
confidence: 99%
“…These findings may not always be applicable to mild‐to‐moderate cholangitis without coagulopathy. One multicenter prospective study and two retrospective studies of mild‐to‐moderate acute cholangitis associated with bile duct stone have shown that the cholangitis cure rate and the hemorrhagic complication rate of single‐session treatment are equivalent to those of two‐session treatment . Stone removal at a single session can shorten the hospital stay, thereby reducing medical cost and the patient's burden.…”
Section: Treatment Of Major Papilla and Removal Of Bile Duct Stonesmentioning
confidence: 99%